Peraturan dan Pengendalian: Menjelaskan Penurunan Produksi Pangan di Jawa 1940-1946 dan Kelaparan 1944-1945 - Pierre van der Eng (Universitas Gadjah Mada, 2020)
The paper discusses the major reasons for the drop in food production in Java during the period of Japanese occupation. Statistics on the acreage and production of six main foodstuff during the year 1940-1946 showed significant reduction of food production in Java after 1942. This reduction is explained as the result of several physical limitation to the production and marketing process of foodstuff. The article explicate several other factors that added to the principal reason for the fall in food production after 1942. The principal reason is laid on the control system of the Javanese rice economy that had reduced the real purchasing price of grain. This resulted in little incentive for peasants to pursue surplus production outside of their household subsistence needs. The only incentive was a negative incentive of forced deliveries.